Mirza Ghalib - Gulazāra; Jagjit Singh, 1941-2011; Saregama India; LC Gift Collection (Library of Congress) ([Kolkata : Saregama India, 1968)
This television serial presents Ghalib's ghazals within the context of his life and his outlook both on the people and the conditions around him.
Copyright notice on disc: Saregam India Ltd.
Discs 1-2 are together in one container.
Not viewed.
Sources used: DVD container; cataloging record from OvOp field office.
Music, Jagjit Singh ; research, Kaifi Azami and Gulzar ; photography, Manmohan Singh ; editing, Subhash Sehgal.
LC Gift Collection.
Keywords: Ghalib, Mirza Asadullah Khan, -- 1797-1869 -- Drama; Poets, Urdu -- 20th century -- Biography -- Drama; Poets, Persian -- 20th century -- Biography -- Drama; Fiction television programs; Television series; Biographical television programs